Visual Analysis of Research Hotspots in Matcha and Research Progress in Its Efficacy - WANG Yuepeng, GENG Zhanhui, ZHENG Zhiqiang, CUI Yan, YANG Liu (Shipin Kexue)
Matcha is a micronized green tea product, which has a unique flavor and taste due to its special processing technique and is widely used in foods. This article examines the progress that has been made in the past decade in matcha research, and analyzes the hot topics and trends in research articles through visual analysis. Based on keyword density analysis, it summarizes the bioactive substances and health benefits of matcha. The caffeine and tea polyphenols in matcha can refresh the mind on their own, they can also work synergistically with theanine to enhance cognitive capacity and reduce anxiety. The tea polyphenols contained in matcha can inhibit the viability of cancer cells through various mechanisms, and reduce the incidence of diseases such as diabetes and cardiovascular diseases. Secondly, the changes in bioactive substances during the production and processing of matcha are elaborated and summarized. Finally, future prospects for the development and application of matcha in foods are discussed. Matcha is a traditional Chinese tea product with high health value. Studying its development trend and elucidating its application in foods will help to enhance its industrial value and provide a theoretical basis for the future development of matcha-based functional foods.